Cornish Copper Mining 1795-1830: Economy, Structure and Change. (1st May 2006) - Lewis, Jim
In his book Cornwall Philip Payton comments on the early industrialization of the Cornish economy, lamenting that 'the complex experience of Cornish industrialisation [has been] marginalised and dismissed in gross oversimplification' and underlining 'the increased interest in comparative regional industrialisation'. He continues this theme in Cornish Studies: Ten, suggesting that Cornwall's failure to receive full recognition for its contribution to the Industrial Revolution is fed by 'a sketchy knowledge of Cornish mining history' amongst scholars. Gill Burke and Peter Richardson have suggested that 'for too long the history of Cornish mining has been characterised by provincialism and anecdotalism'. This overview is intended to look at copper mining in the round and to place it within a broad context. The article contains a brief comparison of Cornwall's copper and tin economies, supported by statistics in the appendix. The period reviewed covers war and peace and strong, sustained growth in British industrial production. The letterbooks of William Jenkin (mineral agent to the Lanhydrock estate and later copper agent to the smelters Williams Grenfell) have been heavily used in researching this article and, where possible, cross checking has confirmed the information they contain.